THE EFFECT OF USING BIG BOOK MEDIA ON THE READING ABILITY OF GRADE II STUDENTS OF SDN 68 PALEMBANG - Parmai Yanti; Noviati (Universitas PGRI Palembang, 2024)
The effect of using big book media on the reading ability of class II students at SDN 68 Palembang aims to determine the effect of using big book media on students' valid and practical reading ability. The type of research used is quantitative. with this type of Quasi Experimental research using saturated sampling techniques. Based on the results of data analysis and research discussion, it can be concluded that there is a significant influence on the use of big book media on students' reading ability in class II of SD Negeri 68 Palembang. Based on the results of research that has been carried out, it is stated that there are differences in Indonesian language learning outcomes between classes that were given treatment and those that were not given treatment, which can be seen from the average score in the experimental class of 85.57, while the average score of the control class was 77.62. To find out the comparison between the two classes, an Independent T Test was carried out, which sig (2 tailed) 0.000 < 0.05 or and control class